Quantitative basic residue requirements in the cleavage-activation site of the fusion glycoprotein as a determinant of virulence for Newcastle disease virus. - Glickman, R L (1988)
Newcastle disease virus exhibits a wide range of pathogenicity and virulence which, as with all paramyxoviruses, is directly related to the cleavability of a precursor (F0) of the fusion glycoprotein by cellular proteases. Sequence analyses of the cleavage site of several virulent and avirulent isolates of the Newcastle disease virus serotype reveal a correlation between virulence or pathogenicity and a high content of basic amino acid residues at the cleavage site. A similar correlation has been seen for other paramyxoviruses.